The Transmission of Light Through Cylindrical Mirror Light Pipe - Woon, Hai Song (1999)
A mirror light pipe (MLP) is an optical device consisting of a metallic reflective closed wall structure with highly transparent open ends. Light falling on the entrance is transmitted through the pipe to the exit by multiple reflections off the inner walls and used at the end. The spectral transmission through silver, aluminium and gold-coated inner walls of cylindrical mirror light pipes has been calculated theoretically based on the Swift and Smith model. The experimental data is also collected for MLP which is made by silverlux. The transmission is dependent upon the angle of incident light and the wavelength of incoming radiation. All pipes show a decrease in the spectral transmission of solar spectrum with an increase in the angle of incidence and the length of the pipes.